I squanch my family representations of male-to-male relationships in Rick and Morty - Saudi, Joseph Christopher Gutierrez 1997-; Guieb, Eulalio R., III (2018)
"This study examines how representation on television plays into the suppression and reinforcement of gender norms. Specifically, this study examines under a feminist lens the representations of male-to-male relationships in a family in adult television cartoons. This study asks if and how the representations of male-to-male relationships in the family of the protagonists of the adult animated television comedy, Rick and Morty, conform to dominant conventions of gender. Using content analysis with a combination of quantitative and qualitative approaches, this research studies all 31 episodes of seasons one to three of Rick and Morty. This research specifically looks at the narratives in the program, particularly the conflicts and resolutions to these conflicts among the male family members of the protagonists' family, as well as the other conflicts in which these characters are involved and the resolutions to these conflicts. It also looks at these characters' physical characteristics, and behavioral characteristics in terms of their actions. This study uses Stuart Hall's concept of representation, Roland Barthes' concept of myth, Judith Butler's theory of gender performativity, and Tony Coles' theoretical model of masculinities, which is based on Raewyn Connell's theories on hegemonic masculinity and Pierre Bourdieu's concepts of capital, habitus, and fields, to analyze the representations of these characters and their relationships and to determine if and how these representations suppress or reinforce dominant gender norms."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Gay men; Gay couples; Rick and Morty (Television program).